Penerapan Pembelajaran Aqidah Akhlaq melalui Pendekatan Talaqqi di MA Ma’arif NU Kepung Kediri - Abdul Ghoni (LPPM IAI Hasanuddin Pare-Kediri, 2017)
This paper wanted to find and find the similarities between civic religion which became the theme of the discussion of Bellah with the concept of Pancasila which became the ideology, the philosophy of life of the Indonesian nation. The author uses the method of content analysis with deductive approach By using the glasses Robert N. Bellah in this study, is expected to find the intersection between the two great concepts. Civil religion that emphasizes public piety and Pancasila with plurality and plurality, will be a beautiful blend in the life of nation and state.